Penyebab dan Dampak Kecelakaan, serta Solusi Keselamatan di Proyek Konstruksi Periode 2016 -2020: Tinjauan Literatur - ferdinand fassa (Universitas Teuku Umar, 2021)
Construction projects escalation bring potential construction accident rates. The study aims to identify cause of construction accident factors, impacts and solutions to reduce accidents in construction project. A Literature Review method was used in this study. Based on the Literature Review, 11 main factors were identified in contributing construction accidents, such as: unsafe actions, unsafe behavior; fatigue, lack of concentration, stress; unsafe conditions, unsafe / dangerous environments; poor PPE quality, poor tools quality; pressure due to tardiness; due to third parties, hot weather, seasons; project complexity & OSH knowledge and training; supervision & inspection; management commitment; leadership; clarity of duties and responsibilities. Solutions to reduce the rate of work accidents by implementing of Safety Management System, such as: Increased Stakeholders roles; Leadership & Organizational Improvement; Increased Information, Communication & Technology; Increased Safety Training; Commitment to allocating SMS costs. Identified caused factors, impacts and solutions can be further analyzed by academics to produce detailed study, and also help in determine strategies for planning construction safety management effectively